1982
DOI: 10.1038/clpt.1982.202
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of complex ventricular arrhythmias by oral flecainide

Abstract: The effectiveness and safety of oral flecainide for suppression of complex ventricular arrhythmias was tested in nine patients in a short-term (4 wk), single-blind, placebo-controlled experiment. The prevalence of multiform premature ventricular complexes (PVCs), couplets and nonsustained ventricular tachycardia (VT) (less than 3 PVCs at rate less than 100/min) was determined by 48-hr Holter monitoring on placebo and flecainide (200 to 300 mg b.i.d.) therapy. Multiform PVCs/hr were reduced by 96% in eight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The percentage reduction achieved in this study was much higher than the limit set by these authors. These results are similar to those obtained by other investigators who found between 90 and 100% suppression in the frequency of VPCs during flecainide therapy (Anderson et al, 1981;Duff et al, 1981;Granrud et al, 1981;Bluschke et al, 1982;Duran et al, 1982;Hodges et al, 1982;Klempt et al, 1982;Abitbol et al, 1983;Salerno et al, 1983). In this study, a Sinus rhythm b Ventricular tachycardia flecainide reduced the number of episodes of VT/S (repetitive VPCs) in 7 out of 10 patients but this did not reach statistical significance.…”
Section: Efficacy Against Ventricular Arrhythmiassupporting
confidence: 92%
See 1 more Smart Citation
“…The percentage reduction achieved in this study was much higher than the limit set by these authors. These results are similar to those obtained by other investigators who found between 90 and 100% suppression in the frequency of VPCs during flecainide therapy (Anderson et al, 1981;Duff et al, 1981;Granrud et al, 1981;Bluschke et al, 1982;Duran et al, 1982;Hodges et al, 1982;Klempt et al, 1982;Abitbol et al, 1983;Salerno et al, 1983). In this study, a Sinus rhythm b Ventricular tachycardia flecainide reduced the number of episodes of VT/S (repetitive VPCs) in 7 out of 10 patients but this did not reach statistical significance.…”
Section: Efficacy Against Ventricular Arrhythmiassupporting
confidence: 92%
“…In this study, a Sinus rhythm b Ventricular tachycardia flecainide reduced the number of episodes of VT/S (repetitive VPCs) in 7 out of 10 patients but this did not reach statistical significance. In other reports there has been a reduction or elimination of repetitive VPCs by an average of 90-100% (Anderson et al, 1981;Duff et al, 1981;Duran et al, 1982;Hodges et al, 1982;Salerno et al, 1983). Furthermore, it has been shown that oral flecainide is more effective than mexiletine (Klempt et al, 1982), quinidine (Morganroth et al, 1983;Salerno et al, 1983) and disopyramide (Kjekshus et al, 1984) in suppressing total VPCs and repetitive VPCs.…”
Section: Efficacy Against Ventricular Arrhythmiasmentioning
confidence: 95%
“…Harrison et al (1981) classified it as a class Ic agent since it has little or no effect on the duration of repolarisation. The antiarrhythmic effectiveness of flecainide has been well documented particularly against ventricular arrhythmias (Duff et al, 1981;Duran et al, 1982;Hodges et al, 1982).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…The absence of trend of change in any of the baseline haemodynamic variables during the control period confirmed the haemodynamic stability of each group. The therapeutic ranges for plasma levels of lignocaine, disopyramide and flecainide are 1-5 ,ug ml-', 2-5 ,ug ml-' and 200-800 ng ml-1 respectively (Bigger, 1980;Grossman et al, 1969;Niarchos, 1976;Koch-Weser, 1979;Anderson et al, 1981;Duran et al, 1982;Hellestrand et al, 1982;Hodges et al, 1982). These were achieved throughout the study, with plasma disopyramide close to the upper limit.…”
Section: Discussionmentioning
confidence: 87%
“…Flecainide, a new class 1C antiarrhythmic agent is an effective broad spectrum anti-arrhythmic (Hellestrand et al, 1982;Hodges et al, 1982;Anderson et al, 1981;Duff et al, 1981;Duran et al, 1982;Anderson et al, 1984). In common with other class 1 agents it induces mild depression of cardiac function in stable coronary artery disease (Legrand et al, 1983;Serruys et al, 1983;Josephson et al, 1984).…”
Section: Introductionmentioning
confidence: 99%